Vooruit ! : voor volksheil en eerlijkheid. (Antwerpen : H. Ernest, 1877)
Beheer/Administratie: M. Dam, Schermersstraat 4, Antwerpen ; Apostelstraat 14, Antwerpen (31 maa.1877)Drukker/Drukkerij: H. Ernest, Hopland 32, Antwerpen ; Mees en Cie, Apostelstraat 14, Antwerpen (31 maa.1877)
Niet consulteerbaar
Periodiciteit: wekelijks
Eerste nummer: 1872
Nederlands
Krant
Keywords: antiklerikalisme; liberale pers; krant